The New Goal: How can We Facilitate Financial Flows to Fragile Contexts in the Horn of Africa and the Sahel? - Chilambe, Pedro; Mascarenhans, Martina (CGIAR System Organization, 2024)
The document examines the challenges and opportunities in climate financing for fragile contexts in the Horn of Africa and the Sahel. Released during COP29, it analyzes financial flows to the Agriculture, Forestry, and Land Use (AFOLU) sector and highlights the significant financing gaps faced by vulnerable regions amid climate and conflict crises. The policy brief emphasizes the need for improved accessibility, transparency, and equity in climate finance mechanisms, advocating for streamlined processes and capacity strengthening to help countries cost their adaptation and mitigation needs. It also underscores the importance of prioritizing adaptation funding, particularly for women, youth, and marginalized groups in conflict-affected areas, while promoting sustainable and inclusive financing models like grants over loans. By bridging these gaps, the initiative aims to enhance resilience and empower local aims to enhance resilience and empower local communities in tackling climate challenges.